Gender classification based on asian faces using deep learning - Janahiraman T.V.; Subramaniam P. (Institute of Electrical and Electronics Engineers Inc., 2023)
Face recognition; Human computer interaction; Image classification; Learning algorithms; Natural language processing systems; Neural networks; Speech recognition; Systems engineering; Convolutional neural network; Gender classification; Learning architectures; Learning frameworks; NAtural language processing; Recognition accuracy; Recognition process; TensorFlow; Deep learning